Evolução técnica do transplante de intestino e multivisceral - Guilherme Costa (2015)
Introduction: Intestinal and multivisceral transplantation are considered the biggest achievements in solid organ transplantation over the last decades. This study analyzes the technical evolution and options of different transplant modalities, discusses the incorporation of new surgical techniques, and evaluates the clinical progress of patients who received transplants with isolated or composite intestinal allografts. Methods: We conducted a retrospective study of 496 consecutive patients who received 551 intestinal transplants at the University of Pittsburgh Medical Center (UPMC), Pittsburgh, Pennsylvania, United States of America between May 1990 and May 2010. Allograft modalities depended on the extension of the disease and the recipient’s clinical characteristics. Of the 551 transplanted allografts, 282 (51%) were isolated intestine and 269 (49%) were composite grafts, including pancreas-intestine, liver-intestine, multivisceral, or modified multivisceral allografts. Fifty–four patients received second transplants and one received a third transplant. Results: Technical modifications uncovered during the study included donor technique, allograft preparation on back table, techniques dependent on anesthesia advances, and surgical technique. Surgical techniques evolved in parallel with immunosuppression protocols as they changed to use more efficient and less toxic drugs. Therefore, the improvement seen in patient and allograft survival was a result of advances in both surgical technique and immunosuppression protocols. The follow-up period, varying from six months to 20.7 years, showed that 287 patients (58%) survived. Of the survivors, 202 survived beyond five years, 46 beyond 10 years, 13 beyond 15 years, and two surpassed the 20 year landmark. Over the last 10 years, survival significantly improved (p<0.001), with one-, five-, and 10-year patient survival rates of 90%, 68%, and 60% respectively, and 86%, 55%, and 48% graft survival rates, respectively. Liver intestine allografts showed better survival compared to isolated intestine allografts. Induction of immunosuppression and/or pre-conditioning protocol did not alter the risk of graft loss due to rejection of the liver-free allografts. Patients two- to 18-years-old and those older than 50 at the time of transplantation had the highest survival rates. Patients receiving multivisceral allografts showed a significantly higher (p< 0.05) rate of fatal infections compared to patients receiving other types of allografts. Liver-intestine allograft recipients showed the highest survival rates. Positive HLA cross-match did not affect graft survival. Conclusions: The improved survival rates and reduced rates of post-operative complications of grafts and patients who underwent intestinal or multivisceral transplantation can be attributed to innovations in surgical techniques during the study period. These innovations were associated with progress in immunosuppressive strategies and in clinical-anesthetic management.